Rahasia komunikasi yang efektif dalam menstimulasi perkembangan sektor perbankan syariah - Kharimah, Firdha Lailatul (Maliki Interdisciplinary Journal, 2024)
This research aims to discover explotiments regarding the implementation of effective communication strategies can prolive the development of the Sharia banking sector. This research uses a qualitative method through a literature study with a descriptive approach. One of the progress indicators lies in economic development that is contributed from financial institutions, especially in the Shariah banking sector. To pronounce economic growth, sharia banking is also necessary to continue growing and growing. In this case, effective communication strategies are needed for its role. There are two kinds of communication related to internal and external parties to be maximized by Sharia banking with effective implementation of strategies, ie internal communication and external communications.